What about us? Exploring small to medium Australian not for-profit firms and knowledge management. Issue 1 (8th February 2016) - Hume, Craig; Hume, Margee
Abstract : Purpose: – The aim of this paper is to research the practice of knowledge management (KM) in not-for-profit (NFP), small and medium enterprises (SMEs) to identify gaps in the current body of knowledge. Previous work has been conducted in small, medium and large enterprises; however, NFP SMEs have been underexamined. Given the prevalence of NFP, SMEs' further research is warranted. Design/methodology/approach: – Using a case study methodology, this research advances previous KM work (Hume and Hume, 2008). Based on previous work in SMEs, KM and the application to NFP organizations, this work offers a set of propositions related to strategic development of KM in NFP organizations with multiple data sources across hierarchical levels sought and analyzed within each of the case studies. This process provided data variation. Collection continued until theoretical saturation was achieved. The paper supports analysis with the use of Leximancer 3.0 and offers a unique approach to qualitative research using textual and narrative analysis. Findings: – This paper explores the definition of knowledge, the importance of knowledge planning, capture and diffusion and offers development in NFP SMEs. The paper concludes by introducing the link between KM and internal marketing to address the importance of cultural and social issues of "me" which are central to knowledge capture, renewal and sustainable KM in NFP organizations. The paper introduces socialization strategies and informal knowledge capture specific to the transient, volunteer and permanent employee mix in NFP organizations and introduces the notion of understanding the significance of social mission to employees and volunteers in the embodiment of KM. Research limitations/implications: – This study has aimed to access all empirical articles in the field of KM in SMEs. To ensure the consideration of the advancement in wireless, mobile computing technology and smartphones as KM support, articles from 2005 onwards were primarily sought. This search restriction has limited the role of earlier works in the research. It is arguable that the sample cases may not offer a comprehensive coverage of all NFP firms, with the qualitative approach further limiting the generalization of the findings. Originality/value: – To the best of the authors' knowledge, KM has been applied specifically in very few NFP SME firms, with scant exploration of the constructs of socialization, social mission and informal knowledge structure in NFP considered or previously published in academic journals.